Board structure in listed firms: evidence from an emerging economy - Oba, Beyza; Tigrel, Elvin; Sener, Pinar (Emerald Group Publishing Ltd, 2014)
Purpose - This paper aims to understand the determinants of board structure of listed firms at institutional, industry and firm levels within an emerging economy. At the institutional level, the paper explores laws, managerial culture and the role of state in instituting and endorsing corporate governance practices. At the firm level, ownership patterns (family and non-family), experience in the capital markets, age and size of the firms are studied to find out the relation between these variables and the board structure. Design/methodology/approach - The research domain of the study is listed firms operating on the Istanbul Stock Exchange. The data for the study are collected at two phases; at the first phase, compliance reports, annual reports, articles of association and annual shareholders' meeting reports of each firm in the sample are analyzed. At the second stage, secondary data are used for understanding the dynamics of Turkish institutional context. Findings - The results of this study reveal that boards of directors of listed Turkish firms comply with the governance practices instituted by state agencies, except on issues as independent members and committees that will influence the majority owners' control domain and private benefits. Originality/value - This paper draws attention on institutional context and argues that good governance instruments developed for Anglo-Saxon stock market-controlled business systems provide limited explanation for an emerging economy that is characterized by close cooperation between the state, family-owned businesses and financial markets. The study offers insight to policy makers at a national level, interested in developing corporate governance principles regarding boards of directors of listed firms.
Keywords: Corporate Governance; Turkey; Boards Of Directors; Board Structure; Board Composition; Emerging Economy; Independent Directors; Investor Protection; Corporate-Ownership; Audit Committee; Ceo Tenure; Determinants; Size; Performance; Entrenchment; Organization